Polymorphisms of the FCN2 Gene 3’UTR Region and Their Clinical Associations in Preterm Newborns - Świerzko, Anna S.; Jarych, Dariusz; Gajek, Gabriela; Chojnacka, Karolina; Kobiela, Paulina; Kufelnicka-Babout, Maja; Michalski, Mateusz; Sobczuk, Katarzyna; Szala-Poździej, Agnieszka; Matsushita, Misao; Mazela, Jan; Domżalska-Popadiuk, Iwona; et al. (Frontiers in Immunology, 2021)
Ficolin-2 is regarded as an important innate immunity factor endowed with both lectin (carbohydrate recognition) qualities and ability to induce complement activation. The aim of this study was to investigate the association of the FCN2 3’-untranslated region (3’UTR) polymorphisms with ficolin-2 expression and perinatal complications in preterm neonates. The sequencing analysis allowed us to identify six 3’UTR polymorphisms with minor allele frequency (MAF) >1%: rs4521835, rs73664188, rs11103564, rs11103565, rs6537958 and rs6537959. Except for rs4521835, all adhered to Hardy-Weinberg expectations. Moreover, rs6537958 and rs6537959 were shown to be in perfect linkage disequilibrium (LD) with nine other genetic polymorphisms: rs7040372, rs7046516, rs747422, rs7847431, rs6537957, rs6537960, rs6537962, rs11462298 and rs7860507 together stretched on a distance of 1242 bp and very high LD with rs11103565. That DNA region was shown to bind nuclear extract proteins. The polymorphisms at rs4521835 and rs73664188 were found to influence serum ficolin-2 concentration significantly. All polymorphisms identified create (together with exon 8 polymorphism, rs7851696) two haplotype blocks. Among 49 diplotypes created from rs7851696 (G>T), rs4521835 (T>G), rs73664188 (T>C), rs11103564 (T>C), rs11103565(G>A) and rs6537959 (T>A), twenty two occurred with frequency >1%. Two diplotypes: D13 (GTTTGT/GGTCGT) and D10 (GTTTGT/GGTCGA), were significantly more frequent among preterm neonates with early onset of infection and pneumonia, compared with newborns with no infectious complications (OR 2.69 and 2.81, respectively; both p<0.05). The minor (C) allele at rs73664188 was associated with an increased risk of very low (≤1500 g) birthweight (OR=1.95, p=0.042) but was associated with the opposite effect at rs11103564 (OR=0.11, p=0.005).